International cooperation is a perspective for the development of scientific researches in law - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is about the importance of international cooperation for the development of new scientific researches in law. If the national system will be better integrated into the international scientific community, will appear more additional opportunities for effective and efficient scientific activity